1998
DOI: 10.4037/ajcc1998.7.3.205
|View full text |Cite
|
Sign up to set email alerts
|

Effect of neuromuscular blockers and opiates on the cerebrovascular response to endotracheal suctioning in adults with severe head injuries

Abstract: BACKGROUND: Intracranial hypertension occurs in response to routine procedures such as endotracheal suctioning in patients with severe head injuries. In some patients, the intracranial pressure does not immediately return to baseline levels. OBJECTIVES: To examine the effect of drug administration on cerebrovascular response to endotracheal suctioning in adults with severe head injuries. METHODS: Seventy-one subjects were divided into 3 groups: those who received no drugs, those treated with opiates only (morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 0 publications
1
22
0
Order By: Relevance
“…However, the physiological effects of many of these interventions are largely unknown, and research in paediatric intensive care (PIC) is extremely limited. There is some evidence to show that in adult intensive care, these care interventions can produce significant adverse effects in brain‐injured patients (Mitchell et al , 1981; Fisher et al , 1982; Parsons and Ouzts Shogan, 1984; Parsons and Wilson, 1984; Parsons et al , 1985; Garradd and Bullock, 1986; Lee, 1989; Ersson et al , 1990; Campbell , 1991; Rudy et al , 1991; Crosby and Parsons, 1992; Paratz and Burns, 1993; Jones, 1995; Brucia and Rudy, 1996; Kerr et al , 1998; Gemma et al , 2002). However, this evidence is inconclusive in relation to the effects of many essential nursing care interventions in head‐injured patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, the physiological effects of many of these interventions are largely unknown, and research in paediatric intensive care (PIC) is extremely limited. There is some evidence to show that in adult intensive care, these care interventions can produce significant adverse effects in brain‐injured patients (Mitchell et al , 1981; Fisher et al , 1982; Parsons and Ouzts Shogan, 1984; Parsons and Wilson, 1984; Parsons et al , 1985; Garradd and Bullock, 1986; Lee, 1989; Ersson et al , 1990; Campbell , 1991; Rudy et al , 1991; Crosby and Parsons, 1992; Paratz and Burns, 1993; Jones, 1995; Brucia and Rudy, 1996; Kerr et al , 1998; Gemma et al , 2002). However, this evidence is inconclusive in relation to the effects of many essential nursing care interventions in head‐injured patients.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Kerr et al (1998) in a large experimental study of 71 head-injured adults comparing different drug treatment with ETS found that patients treated with no sedative drugs displayed the classic 'stair-step' ICP increase pattern with ETS, whereas those treated with opiates and neuromuscular blockade (no cough) showed a flat response to ETS, with little change in ICP, demonstrating the effectiveness of levels of sedation and paralysis on patient's response to ETS. So, two papers concluded that if patients cough during ETS then their ICP is more pronounced.…”
Section: The Effect Of Coughing During Ets On the Icp Risementioning
confidence: 93%
“…They found that ETS increased ICP, and this increase was more pronounced when sedation was inadequate (p < 0Á0001). Kerr et al (1998) specifically studied the effect of neuromuscular blockade and opiates on the cerebrovascular response to ETS in 71 severe head-injured adults using a quasi-experimental design (no randomization). These patients were divided into three groups: group 1, no drugs; group 2, opiates only and group 3, opiates + neuromuscular blockade.…”
Section: The Effect Of Pharmacological Agents On Icp Changes Induced mentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is also important to prevent sudden drops in blood pressure and cerebral perfusion by giving too much sedation; therefore, a balance needs to be achieved (Hall, 1997). The use of neuromuscular blockade drugs, such as rocuronium or atracurium, may be given prior to ETS as they reduce the incidence of coughing which will cause a rise in ICP (Palmer, 2000;Kerr et al, 1998). Suctioning should be performed if clinically indicated, and interventions of preoxygenation and sedation are recommended.…”
Section: Respiratorymentioning
confidence: 99%